(untitled) (Research, Society and Development, 2024)
Introduction: Pharmacotherapy in neonates is challenging due to the immaturity of the organs responsible for the absorption, metabolism and excretion of medications. Objective: The objective of the present study is to carry out an integrative review of the literature on the main problems related to medications in neonatal intensive care units and the importance of pharmaceutical assistance to correct, minimize and prevent the occurrence of DRPs in NICUs. Method: A bibliographic survey was done in Google Scholar, Scientific Electronic Library Online (Scielo), Latin American and Caribbean Literature in Health Sciences (LILACS), and PubMed databases. Results: The main DRPs identified were prescription and administration errors linked to the lack of protocols and infrastructure. Premature neonates use medications with different specialties, many of these medications are classified as Off-Label (OL) and Unlicensed (UL). The Pharmaceutical Recommendations (RFs) were mainly related to dose adjustment, interval, and standard concentration. The RFs carried out had a good percentage of acceptance by the multidisciplinary team. Conclusion: The study showed that DRPs are very common in patients admitted to the NICU, and reinforces the importance of the pharmacist to correct, minimize, and prevent these errors from happening, ensuring the safety and effectiveness of pharmacotherapy in NBs.